Surgical versus conservative treatment following acute rupture of the Achilles tendon: is there a pedobarographic difference? - Karaaslan F; Mermerkaya MU; Çıraklı A; Karaoğlu S; Duygulu F (Dove Medical Press, 2016)
Fatih Karaaslan,1 Musa Uğur Mermerkaya,1 Alper Çıraklı,2 Sinan Karaoğlu,3 Fuat Duygulu21Department of Orthopaedics and Traumatology, Faculty of Medicine, Bozok University, Yozgat, Turkey; 2Department of Orthopaedics and Traumatology, Kayseri Training Hospital, Kayseri, Turkey; 3Department of Orthopaedics and Traumatology, Memorial Kayseri Hospital, Kayseri, TurkeyIntroduction: Controversy remains regarding the optimal treatment method and postoperative rehabilitation of acute Achilles tendon ruptures. In this study, pedobarographic assessments of surgical and conservative treatments were compared.Material and methods: A prospective assessment was made of 16 patients (eight surgical, eight conservative) and eight healthy controls using a plantar pressure measurement system. Biomechanical gait parameters were obtained using the Footscan dynamic gait analysis system. Kruskal–Wallis and Mann–Whitney U-tests were used for the evaluation of data.Results: Nineteen males and five females were assessed, with an average age of 42.0±11.9 years. Follow-up was completed in 16 patients. No statistically significant difference was determined between the two treatment groups with regard to the gait analysis, but a difference was observed with the control group (P<0.001). All patients were able to resume their prior activities after 6 months and regained normal ranges of motion, with a high rate of satisfaction. Most of the patients (75%) were able to return to their pre-injury level of activities.Conclusion: Satisfactory results were obtained through conservative treatment of acute ruptures of the Achilles tendon. No significant differences or complications were observed in the group managed conservatively versus the group treated surgically. Further studies including 3D gait analyses and tendon biomechanical research are required to further investigate this issue.Keywords: Achilles tendon, acute rupture, pedobarographic analysis